PERSEPSI REMAJA PADA ROMANTISISME FILM DILAN 1990 - Fais, Farida; Sudaryanto, Edy; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to find out how teenagers perceive dilan film romanticism that premieredthroughout Indonesia since January 25, 2018. The method is descriptive method that aims toprovide a picture of a group of people or symptoms. The ongoing research is carried out bythe method of observation, in-depth interviews and documentation as a technique inobtaining data. The perception results shown by adolescents on Sidokapasan X Kec.Simokerto, Surabaya for the Dilan 1990 films are various, and are measured from differentperspectives. The film, titled Dilan 1990, has an influence on adolescents who are stillunstable.Keywords : Perception, Youth, Movie Theaters.